RECONSTRUCTION OF LEGAL PROTECTION DISTRICT HEAD IN THE ELECTION IMPLEMENTATION OF VALUE-BASED JUSTICE - Kukuh Sudarmanto Alugoro; Gunarto Gunarto; Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Regional Head Election (Election) directly represent the democratic party will choose direct Regional Head, things in the most tangible manifestation of sovereignty in the hands of the people, as well as the most concrete manifestation in the state administration. Therefore, the system and the organization of the elections is a major concern because through compliance and quality system, the organization of the elections are expected to be able to truly realize of, by and for the people. In this election there are six (6) issues, namely: (1) election marred by political money and the high cost. (2) Election marred lack of neutrality and the movement of Bureaucracy. (3) That would create horizontal conflicts. (4) Sustainability Political Dynasty. (5) a single candidate in the elections (closing the independent candidates and all buy all political party) and (6) Role of Head highly strategic to the success of the elections. Based on the background of the problem dissertation problem is formulated as follows : (1) Why legal protection Head in the elections this time has not been based on values of justice (2) any constraints faced regarding the protection Head in the elections this time? and (3) How rekonstruksi Head of legal protection in the implementation of the elections based on values of justice? This research is a qualitative sociological juridical approach (Socio Legal Approach). This research approach based on the existing problems want to find a deep meaning and details of the implementation and assessment rbagai legal aspects of relations with non-legal aspects of the working of the law in society. Legal research sociological research follows the pattern of the social sciences in particular so-called socio Legal research research. This study aims to reveal the legal protection Head tasks in the implementation of the elections based on values of justice. The research findings indicate that the Head of Legal Reconstruction in the implementation of local elections is dialam Article 70 (1) c Undang-- Law Number 10 Year No. I of 2014 on the Election of governors, regents and mayors into Law - Law, reads: in the campaign of the candidate pairs banned involves: c. Village Head or other title / Village and the Village or any other designation. Device Village, direkonstrusikan be a partner in the campaign of candidates allowed to involve: c. Devices district and sub-district, the village chief or other designation / Village and the Village or any other designation / Irish Village. It underlies that Head and devices not yet entered the District specifically, when the authority of Head very strategic in the election. In Article 162 (3) of Law No. 10 of 2016 declared the governor, regent or mayor who will perform the replacement officials in lingkungaa Government of Proponsi or state / city in a period of 6 (six) months from the date of the inauguration must obtain the written approval of the Minister, recontextualised became governor, regent or mayor who will make the turn positions in the Government of the Province or District / Town including the post of Head within a period of one (1) year after the date of the inauguration and must obtain the written approval of the Minister, this reconstruction is conceived mean that the implementation of the budget ( budget Revenue and Expenditure) is one year, so that when mutated or removed six months of his then Head of latent performance. Keywords : Legal Protection Head, Regional Head Election, Justice Values base